Probiotic Species in the Management of Periodontal Diseases: An Overview - Zhang, Yuwei; Ding, Yi; Guo, Qiang (Frontiers in Cellular and Infection Microbiology, 2022)
Periodontal diseases are one of the most common chronic inflammatory diseases of oral cavity, which are initiated and sustained by pathogenic plaque biofilms. Central to the modern periodontology is the idea that dysbiosis of periodontal microecology and disorder of host inflammatory response give rise to degradation of periodontal tissues together, which eventually leads to tooth loss and seriously affects the life quality of patients. Probiotics were originally used to treat intestinal diseases, while in recent years, extensive studies have been exploring the utilization of probiotics in oral disease treatment and oral health care. Probiotic bacteria derived from the genera Lactobacillus, Bifidobacterium, Streptococcus and Weissella are found to play an effective role in the prevention and treatment of periodontal diseases via regulating periodontal microbiota or host immune responses. Here, we review the research status of periodontal health-promoting probiotic species and their regulatory effects. The current issues on effectiveness and safety of probiotics in the management of periodontal diseases are also discussed at last. Taken together, the use of probiotics is a promising approach to prevent and treat periodontal diseases. Nevertheless, their practical use for periodontal health needs further research and exploration.